Hubungan Pola Asuh Makan terhadap Perkembangan Balita di Desa Aneuk Glee Indrapuri Aceh Besar - Arina Latafika; Syukriadi Syukriadi; Jubir Jubir (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
The toddler period is a golden time for children's growth and development. Parental feeding style plays an important role in healthy eating habits and supporting the optimal development of toddlers. This study aims to determine the correlation between parental feeding style towards toddlers’ growth in Aneuk Glee Village, Indrapuri, Aceh Besar. This study used a quantitative method with a cross-sectional design. The population consisted of 85 parents with toddlers. The sample was 46 parents with toddlers selected by using a cluster sampling technique. The data collection was conducted using the Parental Feeding Style questionnaire and the Denver Developmental Screening Test (DDST), which were used to measure toddlers’ growth, with a Cronbach’s Alpha value of 0.60. The data was analysed using univariate and bivariate analysis with the Chi-Square test at a significance level of 0.05. These results of statistical tests showed a correlation between parental feeding style in toddlers’ growth, with a p-value = 0.016 (< 0.05). The findings reveal that a proper parental feeding style contributes to the optimal growth of toddlers. This study recommends that parents increase their knowledge of better nutrition as a promotive and preventive effort to improve the quality of early childhood development.